The Effect of Teaching Mathematics Using The Mcguigan Strategy on The Inductive Thinking Skills of Fifth-Grade Primary School Students (Journal of the College of Basic Education, 2025)
The research aims to identify the impact of teaching mathematics using the McGuigan strategy on the inductive reasoning skills of fifth-grade primary school students. Al-Sahoul Mixed Primary School, affiliated with the General Directorate of Education in Diyala/Al-Khalis District, was intentionally selected. The research sample consisted of (53) male and female fifth-grade students in the second semester of the 2024-2025 academic year. By random selection of the people, group (A) was chosen to be the experimental group that studied according to the McGuigan strategy, with (27) male and female students, and group (C) was chosen to be the control group that studied according to the traditional method, with (26) male and female students. The two groups were rewarded in the following variables: (Intelligence, chronological age, previous knowledge in mathematics, and parents’ educational level), an inductive thinking skills test in mathematics was constructed, consisting of (18) objective paragraphs of the (multiple choice) type, and including (6) skills, which are (determining the causal relationship, representative reasoning, reaching conclusions, determining information related to the topic, recognizing relationships, and analyzing open problems) With (3) paragraphs for each skill, the validity of the test, the difficulty coefficient and the discrimination of its paragraphs were confirmed, and by using the Kuder Richardson equation (KR-20), the value of the reliability coefficient was (0.864). After completing the experiment, the inductive thinking skills test in mathematics was applied to the two research groups (experimental and control), where the statistical program SPSS_20 was used to process the data statistically. The results showed a statistically significant difference at the significance level of (0.05) between the average scores of students in the experimental group and those in the control group on the inductive reasoning skills test, in favor of the experimental group based on the teaching method. In light of the research results, a number of conclusions, recommendations, and proposals were reached.